A method for rapid grain boundary corrosion of a ni-cr-w alloy
By heat treatment to precipitate secondary carbides at the grain boundaries of Ni-Cr-W alloy and then etching them with copper sulfate etchant, the problem of unclear grain boundary display in the prior art was solved, achieving a safe and clear grain boundary etching effect, which supports subsequent microstructure research.
Patent Information
- Application Number
- CN202611375345.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-11-06
AI Technical Summary
Existing etchants are insufficient to clearly and completely reveal the grain boundaries of Ni-Cr-W alloys, affecting grain size assessment and grain morphology observation, and posing safety and environmental pollution risks.
By heat-treating the surface of the Ni-Cr-W alloy to induce the precipitation of secondary carbides at the grain boundaries, the corrosion resistance of the grain boundaries is reduced. Then, copper sulfate etching solution is used to etch the surface and expose the grain boundaries.
Clear corrosion of grain boundaries in Ni-Cr-W alloys was achieved, improving the clarity of grain boundary corrosion, simplifying subsequent microstructure studies, and reducing safety risks and environmental pollution.
Smart Images

Figure CN123045804A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for rapid etching of grain boundaries. Background Technology
[0002] The outlet temperature of the fourth-generation high-temperature gas-cooled reactor reaches over 700℃, and traditional ferritic and austenitic heat-resistant steels can no longer meet its high-temperature service requirements. Therefore, high-temperature nickel-based alloys must be used to manufacture related components. This Ni-Cr-W nickel-based high-temperature alloy can maintain a long-term service temperature of up to 1150℃ in an oxidizing atmosphere. This alloy is strengthened by solid solution with W and Mo elements, using carbides as the second phase for reinforcement. It has a small coefficient of thermal expansion, resulting in components with low thermal stress, and is easy to process and weld. It also possesses good strength, thermal stability, and corrosion resistance, making it the preferred material for large forgings in fourth-generation high-temperature gas-cooled reactors.
[0003] Ni-Cr-W nickel-based superalloys in solid solution state are difficult to clearly visualize using existing etchants due to their high alloy element content and strong grain boundary corrosion resistance. This hinders subsequent microstructure studies, such as grain morphology and size determination. Furthermore, etching of nickel-based alloy grains using aqua regia (HCl:HNO3 = 3:1) is highly volatile and corrosive, posing a threat to personnel safety and environmental pollution. Summary of the Invention
[0004] The purpose of this invention is to solve the problems that it is difficult to clearly and completely display the grain boundaries when using existing etchants to etch Ni-Cr-W alloys, which affects subsequent grain size assessment, grain morphology observation, and the poor safety of grain etching using traditional methods, and is prone to environmental pollution. Therefore, this invention provides a method for rapid etching of grain boundaries in Ni-Cr-W alloys.
[0005] This invention effectively utilizes the grain boundary precipitation characteristics of materials. By precipitating secondary carbides at the grain boundary after heat treatment at a certain temperature, the corrosion resistance of the grain boundary is reduced. The corrosion clarity of the grain boundary is improved by utilizing the characteristic of secondary carbides precipitating in a chain along the grain boundary.
[0006] This invention provides a method for rapid grain boundary corrosion of Ni-Cr-W alloys. The corrosion method described herein can quickly complete grain boundary corrosion and clearly reveal the grain boundaries. Specifically, it is accomplished through the following steps:
[0007] I. Preparation of Ni-Cr-W alloy test samples:
[0008] The surface of the Ni-Cr-W alloy to be tested was subjected to mechanical coarse grinding, fine grinding, polishing, cleaning and drying in sequence to obtain the Ni-Cr-W alloy test sample.
[0009] II. Heat Treatment:
[0010] The Ni-Cr-W alloy test sample was placed in a heat treatment furnace at a temperature of 850℃~950℃ for heat treatment, and then cooled to room temperature with the furnace to obtain the heat-treated Ni-Cr-W alloy test sample.
[0011] III. Preparation of copper sulfate etching solution:
[0012] Add water, concentrated sulfuric acid, copper sulfate pentahydrate, and concentrated hydrochloric acid to a container in sequence, stir well, and you will get a copper sulfate corrosion solution.
[0013] The mass-to-volume ratio of copper sulfate pentahydrate, water, concentrated sulfuric acid, and concentrated hydrochloric acid in step three is 20g:80mL:5mL:150mL;
[0014] IV. Grain boundary corrosion detection:
[0015] The polished surface of the heat-treated Ni-Cr-W alloy test sample is polished again, then cleaned and dried, and then immersed in copper sulfate etching solution for 10s~30s. After etching, the sample is taken out and the etched surface is inspected and observed, thus completing a method for rapid grain boundary etching of Ni-Cr-W alloy.
[0016] The beneficial effects of this invention are:
[0017] I. Based on the characteristics of nickel-based alloys, such as high temperature resistance, oxidation resistance, no phase transformation, and high stability, this invention adds a low-temperature oxidation treatment step, which preferentially oxidizes the originally high-energy grain boundaries. Then, the grain boundaries are clearly and completely exposed by etching with a newly prepared copper sulfate etching solution, which facilitates subsequent research on the as-cast microstructure and provides accurate and reliable testing basis for experimental research, quality problem analysis, and quality control of this type of material.
[0018] II. The method for rapid grain boundary corrosion of Ni-Cr-W alloys according to the present invention can quickly complete grain boundary corrosion and clearly display the grain boundaries;
[0019] Third, the method of the present invention has good display effect and reproducibility, and does not have special requirements for the optical microscope used for observation. It is a relatively ideal method for displaying the grain boundaries of nickel-based alloys in the as-cast state. Attached Figure Description
[0020] Figure 1 Photographs showing the grain size of the sample etched with copper sulfate solution without heat treatment in Comparative Example 1.
[0021] Figure 2 The grain boundary morphology of the sample etched with copper sulfate solution without heat treatment in Comparative Example 1 is shown.
[0022] Figure 3 This is a photograph of the grain size of the sample etched with copper sulfate solution after heat treatment in Example 1.
[0023] Figure 4 This is a low-magnification photograph of the grain boundary morphology of the sample etched with copper sulfate solution after heat treatment in Example 1.
[0024] Figure 5 High magnification photograph of the grain boundary morphology of the sample etched with copper sulfate solution after heat treatment in Example 1;
[0025] Figure 6 A photograph showing the grain size of the sample etched with aqua regia without heat treatment in Comparative Example 2.
[0026] Figure 7 The grain size photograph is shown for the sample etched with copper sulfate solution after heat treatment, as in Comparative Example 3.
[0027] Figure 8 The image shows the grain size of the sample etched with copper sulfate solution after heat treatment, as shown in Comparative Example 4. Detailed Implementation
[0028] Specific Implementation Method 1: This implementation method is a rapid grain boundary corrosion method for Ni-Cr-W alloys, specifically carried out according to the following steps:
[0029] I. Preparation of Ni-Cr-W alloy test samples:
[0030] The surface of the Ni-Cr-W alloy to be tested was subjected to mechanical coarse grinding, fine grinding, polishing, cleaning and drying in sequence to obtain the Ni-Cr-W alloy test sample.
[0031] II. Heat Treatment:
[0032] The Ni-Cr-W alloy test sample was placed in a heat treatment furnace at a temperature of 850℃~950℃ for heat treatment, and then cooled to room temperature with the furnace to obtain the heat-treated Ni-Cr-W alloy test sample.
[0033] III. Preparation of copper sulfate etching solution:
[0034] Add water, concentrated sulfuric acid, copper sulfate pentahydrate, and concentrated hydrochloric acid to a container in sequence, stir well, and you will get a copper sulfate corrosion solution.
[0035] The mass-to-volume ratio of copper sulfate pentahydrate, water, concentrated sulfuric acid, and concentrated hydrochloric acid in step three is 20g:80mL:5mL:150mL;
[0036] IV. Grain boundary corrosion detection:
[0037] The polished surface of the heat-treated Ni-Cr-W alloy test sample is polished again, then cleaned and dried, and then immersed in copper sulfate etching solution for 10s~30s. After etching, the sample is taken out and the etched surface is inspected and observed, thus completing a method for rapid grain boundary etching of Ni-Cr-W alloy.
[0038] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the rough grinding method described in step one involves sequentially grinding the test surface with 180-mesh and 320-mesh sandpaper. All other steps are the same as in Specific Implementation Method One.
[0039] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that the fine grinding method described in step one is: the test surface is repeatedly ground using 600-grit and 1000-grit sandpaper. Other steps are the same as in Specific Implementation Method One or Two.
[0040] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the polishing method described in step one is: polishing is performed on a metallographic polishing cloth using a polishing agent with a thickness of 1.5μm to 2.5μm. The other steps are the same as in Specific Implementation Methods One to Three.
[0041] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the cleaning method described in step one is as follows: the polished surface is cleaned 2 to 3 times with clean water and then with alcohol of 95% or higher. The other steps are the same as in Specific Implementation Methods One to Four.
[0042] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the Ni-Cr-W alloy described in step one is composed of the following elements by mass fraction: C: 0.05%~0.15%, Si: 0.25%~0.75%, Mn: 0.3%~1.0%, P≤0.020%, S≤0.015%, Cr: 20.0%~24.0%, Mo: 1.0%~3.0%, Ti≤0.10%, Al: 0.2%~0.5%, B≤0.015%, Co≤5.0%, Fe≤3.0%, W: 13.0%~15.0%, with the remainder being Ni. The other steps are the same as in Specific Implementation Methods One to Five.
[0043] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the heat treatment time in step two is 1 to 3 hours. The other steps are the same as in Specific Implementation Methods One to Six.
[0044] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that the mass fraction of the concentrated sulfuric acid mentioned in step three is 98%; the mass fraction of the concentrated hydrochloric acid mentioned in step three is 37%. The other steps are the same as in Specific Implementation Methods One to Seven.
[0045] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the polishing method described in step four is as follows: polishing is performed on a metallographic polishing cloth using a polishing agent with a thickness of 1.5μm to 2.5μm. The other steps are the same as in Specific Implementation Methods One to Eight.
[0046] Specific Implementation Method Ten: The difference between this implementation method and Specific Implementation Methods One to Nine is that the cleaning method described in step four is as follows: the polished surface is cleaned 2 to 3 times with clean water and then with alcohol of 95% or higher. The other steps are the same as in Specific Implementation Methods One to Nine.
[0047] The beneficial effects of the present invention are verified using the following embodiments:
[0048] Example 1: A method for rapid grain boundary corrosion of Ni-Cr-W alloys, specifically carried out according to the following steps:
[0049] I. Preparation of Ni-Cr-W alloy test samples:
[0050] The Ni-Cr-W alloy was subjected to mechanical coarse grinding, fine grinding, polishing, cleaning and drying in sequence to obtain Ni-Cr-W alloy test samples;
[0051] The rough grinding method described in step one is as follows: the test surface is repeatedly ground with 180-grit and 320-grit sandpaper in sequence;
[0052] The fine grinding method described in step one is as follows: the test surface is repeatedly ground with 600-grit and 1000-grit sandpaper in sequence;
[0053] The polishing method described in step one is as follows: polishing with a 1.5μm polishing agent on a metallographic polishing cloth;
[0054] The cleaning method described in step one is as follows: clean the polished surface three times each with clean water and 95% alcohol.
[0055] The Ni-Cr-W alloy described in step one is composed of the following elements by mass fraction: C: 0.1%, Si: 0.35%, Mn: 0.5%, P: 0.018%, S: 0.01%, Cr: 22.0%, Mo: 2.2%, Ti: 0.05%, Al: 0.30%, B: 0.01%, Co: 0.1%, Fe: 2.2%, W: 14.3.0%, with the remainder being Ni;
[0056] II. Heat Treatment:
[0057] The Ni-Cr-W alloy test sample was placed in a heat treatment furnace at 930℃ for 3 hours and then cooled to room temperature with the furnace to obtain the heat-treated Ni-Cr-W alloy test sample.
[0058] III. Preparation of copper sulfate etching solution:
[0059] Add water, concentrated sulfuric acid, copper sulfate pentahydrate, and concentrated hydrochloric acid to a container in sequence, stir well, and you will get a copper sulfate corrosion solution.
[0060] The mass-to-volume ratio of copper sulfate pentahydrate, water, concentrated sulfuric acid, and concentrated hydrochloric acid in step three is 20g:80mL:5mL:150mL;
[0061] The concentrated sulfuric acid mentioned in step three has a mass fraction of 98%.
[0062] The concentrated hydrochloric acid mentioned in step three has a mass fraction of 37%.
[0063] IV. Grain boundary corrosion detection:
[0064] The polished surface of the heat-treated Ni-Cr-W alloy test sample is polished again, then cleaned and dried, and then immersed in copper sulfate etching solution for 20 seconds. After etching, the sample is taken out and the etched surface is inspected and observed, thus completing a method for rapid etching of Ni-Cr-W alloy grain boundaries.
[0065] The polishing method described in step four is as follows: polishing with a 1.5μm polishing agent on a metallographic polishing cloth;
[0066] The cleaning method described in step four is as follows: clean the polished surface three times each with clean water and 95% alcohol.
[0067] Comparing with Example 1: The method of etching with copper sulfate solution without heat treatment is carried out in the following steps:
[0068] I. Preparation of Ni-Cr-W alloy test samples:
[0069] The Ni-Cr-W alloy was subjected to mechanical coarse grinding, fine grinding, polishing, cleaning and drying in sequence to obtain Ni-Cr-W alloy test samples;
[0070] The rough grinding method described in step one is as follows: the test surface is repeatedly ground with 180-grit and 320-grit sandpaper in sequence;
[0071] The fine grinding method described in step one is as follows: the test surface is repeatedly ground with 600-grit and 1000-grit sandpaper in sequence;
[0072] The polishing method described in step one is as follows: polishing with a 1.5μm polishing agent on a metallographic polishing cloth;
[0073] The cleaning method described in step one is as follows: clean the polished surface three times each with clean water and 95% alcohol.
[0074] The Ni-Cr-W alloy described in step one is composed of the following elements by mass fraction: C: 0.1%, Si: 0.35%, Mn: 0.5%, P: 0.018%, S: 0.01%, Cr: 22.0%, Mo: 2.2%, Ti: 0.05%, Al: 0.30%, B: 0.01%, Co: 0.1%, Fe: 2.2%, W: 14.3.0%, with the remainder being Ni;
[0075] II. Preparation of copper sulfate etching solution:
[0076] Add water, concentrated sulfuric acid, copper sulfate pentahydrate, and concentrated hydrochloric acid to a container in sequence, stir well, and you will get a copper sulfate corrosion solution.
[0077] The mass-to-volume ratio of copper sulfate pentahydrate, water, concentrated sulfuric acid, and concentrated hydrochloric acid in step two is 20g:80mL:5mL:150mL;
[0078] The concentrated sulfuric acid mentioned in step two has a mass fraction of 98%.
[0079] The concentrated hydrochloric acid mentioned in step two has a mass fraction of 37%.
[0080] III. Grain boundary corrosion detection:
[0081] The polished surface of the heat-treated Ni-Cr-W alloy test sample is polished again, then cleaned and dried, and then immersed in copper sulfate etching solution for 20 seconds. After etching, the sample is taken out and the etched surface is inspected and observed, thus completing a method for Ni-Cr-W alloy grain boundary corrosion.
[0082] The polishing method described in step three is as follows: polishing with a 1.5μm polishing agent on a metallographic polishing cloth;
[0083] The cleaning method described in step three is as follows: clean the polished surface three times each with clean water and 95% alcohol.
[0084] Comparison with Example 2: The method of etching with aqua regia (HCl:HNO3=3:1) without heat treatment is carried out in the following steps:
[0085] I. Preparation of Ni-Cr-W alloy test samples:
[0086] The Ni-Cr-W alloy was subjected to mechanical coarse grinding, fine grinding, polishing, cleaning and drying in sequence to obtain Ni-Cr-W alloy test samples;
[0087] The rough grinding method described in step one is as follows: the test surface is repeatedly ground with 180-grit and 320-grit sandpaper in sequence;
[0088] The fine grinding method described in step one is as follows: the test surface is repeatedly ground with 600-grit and 1000-grit sandpaper in sequence;
[0089] The polishing method described in step one is as follows: polishing with a 1.5μm polishing agent on a metallographic polishing cloth;
[0090] The cleaning method described in step one is as follows: clean the polished surface three times each with clean water and 95% alcohol.
[0091] The Ni-Cr-W alloy described in step one is composed of the following elements by mass fraction: C: 0.1%, Si: 0.35%, Mn: 0.5%, P: 0.018%, S: 0.01%, Cr: 22.0%, Mo: 2.2%, Ti: 0.05%, Al: 0.30%, B: 0.01%, Co: 0.1%, Fe: 2.2%, W: 14.3.0%, with the remainder being Ni;
[0092] II. Grain boundary corrosion detection:
[0093] The polished surface of the Ni-Cr-W alloy test sample is polished again, then cleaned and dried, and then immersed in aqua regia for 20 seconds for corrosion. After corrosion, the sample is taken out and the corrosion surface is inspected and observed, thus completing a method for Ni-Cr-W alloy grain boundary corrosion.
[0094] The polishing method described in step two is as follows: polishing with a 1.5μm polishing agent on a metallographic polishing cloth;
[0095] The cleaning method described in step two is as follows: clean the polished surface three times each with clean water and 95% alcohol.
[0096] The aqua regia mentioned in step two is a mixture of HCl and HNO3 in a volume ratio of 3:1; the mass fraction of HCl is 37% and the mass fraction of HNO3 is 68%.
[0097] Comparative Example 3: The difference between this example and Example 1 is that the mass-to-volume ratio of copper sulfate pentahydrate, water, concentrated sulfuric acid, and concentrated hydrochloric acid in step three is 5g:80mL:5mL:150mL. All other steps and parameters are the same as in Example 1.
[0098] Comparative Example 4: The difference between this example and Example 1 is that the mass-to-volume ratio of copper sulfate pentahydrate, water, concentrated sulfuric acid, and concentrated hydrochloric acid in step three is 5g:80mL:5mL:50mL. All other steps and parameters are the same as in Example 1.
[0099] Figure 1 Photographs showing the grain size of the sample etched with copper sulfate solution without heat treatment in Comparative Example 1.
[0100] Figure 2 The grain boundary morphology of the sample etched with copper sulfate solution without heat treatment in Comparative Example 1 is shown.
[0101] from Figures 1-2 It can be seen that the grain size of the sample etched with copper sulfate solution without heat treatment is not clearly displayed, and twinning is locally displayed after etching, which interferes with the evaluation of the material grain size.
[0102] Figure 3 This is a photograph of the grain size of the sample etched with copper sulfate solution after heat treatment in Example 1.
[0103] Figure 4 This is a low-magnification photograph of the grain boundary morphology of the sample etched with copper sulfate solution after heat treatment in Example 1.
[0104] Figure 5 High magnification photograph of the grain boundary morphology of the sample etched with copper sulfate solution after heat treatment in Example 1;
[0105] from Figures 3-5 It can be seen that the grain size of the sample etched with copper sulfate solution after heat treatment is clearly displayed. After the pre-heat treatment, secondary carbides precipitate on the grain boundaries, which reduces the corrosion resistance of the grain boundaries. The etching with copper sulfate solution makes the grain boundaries fully visible and eliminates twins, providing a basis for grain size rating.
[0106] Figure 6 A photograph showing the grain size of the sample etched with aqua regia without heat treatment in Comparative Example 2.
[0107] from Figure 6 It can be seen that the Ni-Cr-W alloy has strong corrosion resistance, and the grain boundaries cannot be clearly and completely displayed after etching with aqua regia.
[0108] Figure 7 The grain size photograph is shown for the sample etched with copper sulfate solution after heat treatment, as in Comparative Example 3.
[0109] from Figure 7 It can be seen that the amount of copper sulfate pentahydrate in this comparative example is too small, resulting in poor corrosion effect and failure to effectively and clearly corrode the grain boundary positions.
[0110] Figure 8The image shows the grain size of the sample etched with copper sulfate solution after heat treatment, as shown in Comparative Example 4.
[0111] from Figure 8 It can be seen that the amount of copper sulfate pentahydrate and concentrated hydrochloric acid added in this comparative example was insufficient, which caused the overall corrosion performance of the etchant to decline, and it could not effectively corrode the grain boundaries, which seriously affected the effect and accuracy of grain size rating.
[0112] In summary, the beneficial effects of this invention are as follows:
[0113] 1. This invention utilizes the grain boundary precipitation characteristics of Ni-Cr-W alloy. After heat treatment at a certain temperature, secondary carbides are precipitated at the grain boundary position, which reduces the corrosion resistance of the grain boundary. The corrosion clarity of the grain boundary is improved by utilizing the characteristic of secondary carbides precipitating in a chain along the grain boundary.
[0114] 2. This invention targets Ni-Cr-W alloys with reduced grain boundary corrosion resistance by using copper sulfate etching solution to conduct grain boundary oxidation tests, thereby revealing the grain boundaries.
Claims
1. A method for rapid grain boundary corrosion of Ni-Cr-W alloys, characterized in that... The method is specifically implemented according to the following steps: I. Preparation of Ni-Cr-W alloy test samples: The surface of the Ni-Cr-W alloy to be tested was subjected to mechanical coarse grinding, fine grinding, polishing, cleaning and drying in sequence to obtain the Ni-Cr-W alloy test sample. II. Heat Treatment: The Ni-Cr-W alloy test sample was placed in a heat treatment furnace at a temperature of 850℃~950℃ for heat treatment, and then cooled to room temperature with the furnace to obtain the heat-treated Ni-Cr-W alloy test sample. III. Preparation of copper sulfate etching solution: Add water, concentrated sulfuric acid, copper sulfate pentahydrate, and concentrated hydrochloric acid to a container in sequence, stir well, and you will get a copper sulfate corrosion solution. The mass-to-volume ratio of copper sulfate pentahydrate, water, concentrated sulfuric acid, and concentrated hydrochloric acid in step three is 20g:80mL:5mL:150mL; IV. Grain boundary corrosion detection: The polished surface of the heat-treated Ni-Cr-W alloy test sample is polished again, then cleaned and dried, and then immersed in copper sulfate etching solution for 10s~30s. After etching, the sample is taken out and the etched surface is inspected and observed, thus completing a method for rapid grain boundary etching of Ni-Cr-W alloy.
2. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The rough grinding method described in step one is as follows: the test surface is repeatedly ground with 180-mesh and 320-mesh sandpaper.
3. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The fine grinding method described in step one is as follows: the test surface is repeatedly ground with 600-grit and 1000-grit sandpaper.
4. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The polishing method described in step one is as follows: polishing is performed on a metallographic polishing cloth using a polishing agent with a thickness of 1.5μm to 2.5μm.
5. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The cleaning method described in step one is as follows: clean the polished surface 2 to 3 times with clean water and alcohol of 95% or higher.
6. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The Ni-Cr-W alloy described in step one is composed of the following elements by mass fraction: C: 0.05%~0.15%, Si: 0.25%~0.75%, Mn: 0.3%~1.0%, P≤0.020%, S≤0.015%, Cr: 20.0%~24.0%, Mo: 1.0%~3.0%, Ti≤0.10%, Al: 0.2%~0.5%, B≤0.015%, Co≤5.0%, Fe≤3.0%, W: 13.0%~15.0%, with the remainder being Ni.
7. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The heat treatment time in step two is 1 to 3 hours.
8. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The concentrated sulfuric acid mentioned in step three has a mass fraction of 98%; the concentrated hydrochloric acid mentioned in step three has a mass fraction of 37%.
9. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The polishing method described in step four is as follows: polishing with a polishing agent of 1.5μm~2.5μm on a metallographic polishing cloth.
10. The method for rapid grain boundary corrosion of Ni-Cr-W alloy according to claim 1, characterized in that... The cleaning method described in step four is as follows: clean the polished surface 2 to 3 times with clean water and alcohol of 95% or higher.
